2022
DOI: 10.14245/ns.2244658.329
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Neural Stem Cell Therapy for Spinal Cord Injury: Safety, Efficacy, and Future Perspectives

Abstract: Spinal cord injury (SCI) is a devastating central nervous system (CNS) injury that leads to severe disabilities in motor and sensory functions, causing significant deterioration in patients' quality of life.Owing to the complexity of SCI pathophysiology, there has been no effective treatment for reversing neural tissue damage and recovering neurological functions. Several novel therapies targeting different stages of pathophysiological mechanisms of SCI have been developed. Among these, treatments using stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 112 publications
(236 reference statements)
0
6
0
Order By: Relevance
“…Over the past decade, remarkable progress has been made in neural stem cell therapy for SCI [43]. Su et al [44] examined the reprogramming of endogenous scar-forming astrocytes into neurons in the adult mouse spinal cord and found that a high-mobility group of DNA-binding domain transcription factor, SOX2-induced adult neurogenesis can generate mature neurons with features of GABA-ergic interneurons in injured valproic acid (VPA)-treated spinal cords.…”
Section: Modulation Of Neurotrophic Support In Inhibition Neurons Aft...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, remarkable progress has been made in neural stem cell therapy for SCI [43]. Su et al [44] examined the reprogramming of endogenous scar-forming astrocytes into neurons in the adult mouse spinal cord and found that a high-mobility group of DNA-binding domain transcription factor, SOX2-induced adult neurogenesis can generate mature neurons with features of GABA-ergic interneurons in injured valproic acid (VPA)-treated spinal cords.…”
Section: Modulation Of Neurotrophic Support In Inhibition Neurons Aft...mentioning
confidence: 99%
“…Although the number of converted neurons was low, the authors have shown that new neurons were capable of forming synapses with pre-existing CHAT + motoneurons, suggesting potential integration into the local neural network of the injured spinal cord [44]. Currently, cell therapy is one of the effective therapeutic strategies for SCI; however, more studies are required to verify the potential of such treatment to regenerate and/or remyelinate axons, and to incorporate new neural cells into the milieu of a traumatic SCI [43].…”
Section: Modulation Of Neurotrophic Support In Inhibition Neurons Aft...mentioning
confidence: 99%
“…A spinal cord injury (SCI) is an extremely serious neurological event characterized by permanent disability in the body below the injured region. The affected individual’s resulting inability to work (labor) and the costs of long-term treatment impose a heavy financial burden on their family and the wider community [ 1 ]. Despite concerted efforts focused on SCIs in global terms, no effective breakthrough has yet been made toward a cure for the neurological dysfunction caused by an SCI [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the vast literature, which articles have significant value, which countries, institutions, and authors have made important contributions, what are the current research hotspots in the field, and what are the future development directions of this field, all need to be considered and answered. So far, numerous literature reviews and expert opinions have attempted to elucidate the research status and frontiers of stem cell therapy for spinal cord injury ( Tashiro et al, 2021 ; Lee et al, 2022 ; Zipser et al, 2022 ). However, these studies are relatively fragmented and subjectively focused, with insufficient comprehensiveness and systematicness, and less objective and quantitative, which is not conducive to researchers’ overall understanding of the field.…”
Section: Introductionmentioning
confidence: 99%